Subchondral bone attrition may be a reflection of compartment-specific mechanical load: the MOST Study. Issue 5 (17th September 2009) - Neogi, Tuhina; Nevitt, Michael; Niu, Jingbo; Sharma, Leena; Roemer, Frank; Guermazi, Ali; Lewis, Cora E; Torner, James; Javaid, Kassim; Felson, David
Abstract : Introduction: Subchondral bone attrition (SBA), a feature of osteoarthritis, may be caused by excess focal load to bone, and/or inadequate bone quality to withstand loads through the joint. This study evaluated the effects of malalignment, which can cause focal excessive load, and systemic bone density on the presence and incidence of SBA. Methods: The Multicenter Osteoarthritis Study is a cohort of individuals who have or are at high risk of knee osteoarthritis. Baseline alignment and bone mineral density (BMD) measures were assessed. Baseline and 30-month knee magnetic resonance images were graded for SBA (grade 0–3) using the whole-organ magnetic resonance imaging score. The study evaluated the association of alignment in medial and lateral compartments, respectively, and systemic BMD with baseline presence of SBA and incident SBA using logistic regression and adjusting for age, sex and body mass index. Results: Of 1253 participants (mean age 62 years, mean BMI 30, 61% women), 33% had baseline SBA and 44% had knee osteoarthritis. Associations between the presence and incidence of SBA with malalignment in both compartments were noted (odds ratios (95% CI) 2.9 (2.1 to 4.0) and 1.9 (1.2 to 2.9), respectively, for varus knees in the medial compartment; 4.5 (2.8 to 7.1) and 2.1 (1.1 to 4.1), respectively, for valgus knees in the lateral compartment). Low BMD was not associated with SBA. Conclusions: The presence and incidence of SBA are associated with malalignment in a compartment-specific manner, but not with low BMD. SBA may be a marker of increased load experienced by overlying cartilage, which may contribute to increased forces transmitted to the cartilage due to alteration in subchondral bone.